Regulatory RNAs in Autism Spectrum Disorder - Marques, Ana Rita (2019)
A.R.Marques is recipient of a fellowship from BioSys PhD programme (Ref PD/BD/113773/2015 from FCT (Portugal). Patients and parents were genotyped in the context of the Autism Genome Project (AGP), funded by NIMH, HRB, MRC, Autism Speaks, Hilibrand Foundation, Genome Canada, OGI, CIHR, and the Simons Simplex Collection (SSC), a core project of the Simons Foundation Autism Research Initiative (SFARI).